COMPARAÇÃO DAS TÉCNICAS DE IMUNODIFUSÃO EM GEL DE ÁGAR E ELISA NO DIAGNÓSTICO DE BRUCELOSE OVINA EM CABANHAS DA REGIÃO CENTRO-OESTE DO ESTADO DE SÃO PAULO* - Nozaki, C.n. [UNESP]; Megid, J. [UNESP]; Lima, K.c. [UNESP]; Silva, F.f. [UNESP]; Veloso, C.s. [UNESP] (Instituto Biológico, 2024)
Ovine brucellosis due to Brucella ovis is a major cause of economic losses related to milk yield drop, impaired meat production and poor reproductive performance. This study was designed in order to compare the ELISA test and the immunodiffusion in agar gel (AGID) technique in ovine sera from Paulista Ovine Bearer Association registered sheep in the midwest region from São Paulo state, Brazil. The observed results in the AGID test with 2Mercaptoethanol (2-ME) and without 2-Mercaptoethanol and ELISA was correlated to the animals‘ clinical picture. A positivity rate of 1.1% and 12% to AGID, with and without 2-ME, respectively was recorded with 6% of results considered suspicious in ELISA test for the 1,033 analysed serum samples. Considering that ELISA results were of suspect, it cannot be linked with an infected status. The authors reinforce the low agrrement of the tests analysed. The best results were achieved with AGID and ELISA. The associated performance of AGID and ELISA offers a more reliable diagnosis and therefore must be encouraged.

A brucelose ovina, causada pela Brucella ovis, é responsável por perdas econômicas, com prejuízos para a produção de leite, carne e fertilidade do rebanho. O objetivo do trabalho foi comparar as técnicas de Imunodifusão em Gel de Agar e ELISA em soros de ovinos de cabanhas, da região Centro-Oeste do Estado de São Paulo, que registram seus animais na Associação Paulista dos Criadores de Ovinos, correlacionando os resultados obtidos na imunodifusão em gel de ágar sem 2-mercaptoetanol (ID S/2-ME), imunodifusão em gel de ágar com 2-mercaptoetanol (ID C/2-ME) e ELISA ao quadro clínico dos animais. Dos 1.033 soros analisados, observou-se 12% de positivos a ID S/2-ME, 1,1% de positivos a ID C/2-ME e 6% considerados suspeitos ao ELISA. A ID C/2-ME não foi capaz de detectar os animais reagentes ao teste de ELISA. Uma vez que as reações no ELISA foram somente suspeitas, não se pode afirmar que os animais fossem positivos. Os melhores resultados foram observados com a ID S/2-ME e ELISA. Ressalta-se a baixa concordância entre as provas sorológicas avaliadas. A aplicação associada da ID S/2-ME ao ELISA deve ser incentivada para o diagnóstico da brucelose ovina por possibilitar resultados mais confiáveis.
COMPARATION OF THE TECHINIQUE OF IMMUNODIFFUSION IN AGAR GEL AND ELISA TEST IN THE DIAGNOSIS OF OVINE BRUCELLOSIS IN SHEEP IN THE MIDWEST REGION OF SÃO PAULO STATE, BRAZIL
Keywords: Brucella ovis; agar gel immunodifusion; ELISA; ovine brucellosis; 2-mercaptoethanol; Brucella ovis; imunodifusão em gel de ágar; ELISA; brucelose ovina; 2-mercaptoetanol